Cell Cycle Modulation of CHO-K1 Cells Under Genistein Treatment Correlates with Cells Senescence, Apoptosis and ROS Level but in a Dose-Dependent Manner - Riris Istighfari Jenie; Nur Dina Amalina; Gagas Pradani Nur Ilmawati; Rohmad Yudi Utomo; Muthi Ikawati; Annisa Khumaira; Jun- Ya Kato; Edy Meiyanto (Tabriz University of Medical Sciences, 2019)
Purpose: Genistein, a soy isoflavone, exhibits a biphasic effect on cells proliferation with some different effects between ER-alpha and ER-beta. The objective of this present study is to determine the modulatory effect based on cell cycle progression under genistein treatment in combination with 17-β estradiol (E2) on CHO-K1 cells. Methods: The effect of genistein 0.1-100 µM on cells proliferation was examined by MTT assay. The modulation of genistein and estradiol (E2) on cell cycle and apoptosis were observed by using flowcytometry with PI and PI/AnnexinV staining, respectively. Moreover, the effect of genistein and E2 on senescence cells, and ROS level were determined by senescence-associated β-galactosidase (SA β-gal) staining and by using flowcytometry with 2', 7'-dichlorofluorescin diacetate (DCFDA) staining, respectively. The expression level of the cell cycle and senescence protein markers were observed by immunoblotting. Results: Single treatment of genistein at physiologically achievable (low) concentration (<2 µM) induced proliferation of CHO-K1 cells while at a pharmacological (high) concentration (50 and 100 µM) suppressed cells proliferation. Interestingly, treatment of genistein at the physiological concentration in combination with E2 for 24, 48 and 72 h decreased cells viability on CHO-K1 cells compared to untreated cells. Further analysis of the cells showed that 50 µM genistein induced G2/M phase accumulation and induced apoptosis. Moreover, genistein induced cell senescence and increased ROS level. Immunoblotting analysis showed the decreasing of ERalpha, Bcl2, and ppRb protein level upon treatment of 1 µM Gen and 1 nM E2. Conclusion: Our results suggest that the cell proliferation inhibitory mechanism of genistein at pharmacological concentration involved the induction of cell senescence, and the elevation of ROS level. Moreover, the decreased of cells proliferation upon treatment of physiological concentration of genistein in combination with E2 may be correlated with the alteration of ER expression.